2019
DOI: 10.1175/jamc-d-18-0149.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Water Stress under Projected Climate Change across Hydroclimate Gradients in the North-Central United States

Abstract: Water balance influences the distribution, abundance, and diversity of plant species across Earth’s terrestrial system. In this study, we examine changes in the water balance and, consequently, the dryland extent across eight ecoregions of the north-central United States by quantifying changes in the growing season (May–September) moisture index (MI) by 2071–99, relative to 1980–2005, under three high-resolution (~4 km) downscaled climate projections (CNRM-CM5, CCSM4, and IPSL-CM5A-MR) of high-emission scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Climate predictors for the future period from 2011-2040 were averaged from a warm and dry climate scenario predicted by CCSM4 GCM. The CCSM4 moderately captures overall spread of future projections of temperature and precipitation changes across the study area (Adhikari et al 2019a).…”
Section: Future Climate Datamentioning
confidence: 99%
“…Climate predictors for the future period from 2011-2040 were averaged from a warm and dry climate scenario predicted by CCSM4 GCM. The CCSM4 moderately captures overall spread of future projections of temperature and precipitation changes across the study area (Adhikari et al 2019a).…”
Section: Future Climate Datamentioning
confidence: 99%
“…Humans rely on water for drinking and household use, agricultural production, energy generation, industry, navigation, and recreation. Like people, non‐marine species and ecosystems require freshwater for a wide range of physiological and habitat requirements and are increasingly at risk due to declines in the quality and quantity of available water (Adhikari et al, 2019; Jackson et al, 2001; Sabater et al, 2018; Vörösmarty et al, 2010). Regardless of whether a water shortage results from meteorological drought or anthropogenic drivers, when water is scarce, not all demands can be satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing climate modeling experiments-for example, the Coordinated Regional Climate Downscaling Experiment (CORDEX, http://www.cordex.org/), WorldClim dataset project (http://www.worldclim.org/), and the Climate Change, Agriculture, and Food Security research program (CCAFS, http://ccafs-climate.org/downscaling/)---future climate projections are made available over several domains worldwide with a horizontal resolution of up to 12.5 km. Some studies (e.g., [49,50]) demonstrated that dynamical downscaling can be applied to achieve an even larger detail (≤4 km). However, these methods are computationally very intensive and often show performance losses over complex terrains [46,51].…”
Section: Introductionmentioning
confidence: 99%